Designing a capacitated multi-configuration logistics network under disturbances and parameter uncertainty: A real-world case of a drug supply chain - Davood Shishebori; Abolghasem Yousefi Babadi (Journal of Industrial Engineering International, 2018)
This study investigates the reliable multi-configuration capacitated logistics network design problem (RMCLNDP) under system disturbances, which relates to locating facilities, establishing transportation links, and also allocating their limited capacities to the customers conducive to provide their demand on the minimum expected total cost (including locating costs, link constructing costs, and also expected costs in normal and disturbance conditions). In addition, two types of risks are considered; (I) uncertain environment, (II) system disturbances. A two-level mathematical model is proposed for formulating of the mentioned problem. Also, because of the uncertain parameters of the model, an efficacious possibilistic robust optimization approach is utilized. To evaluate the model, a drug supply chain design (SCN) is studied. Finally, an extensive sensitivity analysis was done on the critical parameters. The obtained results show that the efficiency of the proposed approach is suitable and is worthwhile for analyzing the real practical problems.
Keywords: 650; Multi-product; Multi-type transportation links; Multi-vehicles; Multi-configuration; Capacitated logistic network design (LND); Disturbances; Two-stage decomposing heuristic; LP relaxation; Medical service (drug)